Carbon material composite and manufacturing method thereof, pole piece, battery, battery module, battery pack and device
By using a porous carbon material composite containing nitrogen atoms and magnetic particles in the diaphragm of the battery pole sheet, the problem of poor wettability of the electrolyte is solved, the energy density and rate performance of the battery are improved, and the energy density and rate performance of the battery are reduced. The cost.
Patent Information
- Application Number
- CN202210514701.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-05-12
AI Technical Summary
When the prior art improves the energy density and rate performance of the battery, increasing the content of active substances leads to poor wetting properties of the electrolyte, resulting in the inability to perform normally, and causing structural damage and capacity attenuation.
Using a porous carbon material composite containing nitrogen atoms and magnetic particles, the liquid mass transfer ability is improved by forming micron-scale through holes in the membrane, enhancing the infiltration and reflux of the electrolyte, and increasing the depth of electrochemical reactions in the electrode sheet. .
It achieves the improvement of the energy density and rate performance of the battery, reduces the use of current collectors and diaphragms, reduces the cost, and extends the cycle life of the battery.
Smart Images

Figure CN115832238B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a carbon material composite and a manufacturing method thereof, a pole piece, a battery, a battery module, a battery pack and a device. Background Art
[0002] At present, with the continuous development of science and technology, lithium-ion batteries, metal lithium batteries and other batteries are widely used in various electronic devices such as mobile phones, cameras, laptops and other portable small mobile devices, electric vehicles, energy storage systems and other large devices with high power and high energy requirements. As a result, the requirements for battery performance are getting higher and higher, especially the energy density of batteries. Therefore, how to improve the energy density of batteries has become one of the research hotspots.
[0003] In order to improve the energy density of the battery, for example, a method of increasing the content of active materials to increase the thickness of the battery pole piece is considered. This method can increase the amount of active materials loaded on the pole piece surface per unit area, which is very beneficial to improving the specific energy of the battery. However, in the process of actual application, if the thickness of the battery pole piece is increased by simply increasing the content of active materials, the electrolyte is difficult to penetrate into the active materials close to the pole piece surface, which makes the wettability of the electrolyte worse, resulting in the active materials close to the current collector being almost unable to participate in the electrochemical reaction, resulting in the inability to function normally. On the other hand, the active materials far away from the current collector are deeply discharged, which in turn causes structural damage during long cycles, exacerbating capacity attenuation, resulting in poor high current rate performance and poor cycle performance of the pole piece. Summary of the invention
[0004] The present application is developed in view of the above situation, and its purpose is to provide a carbon material composite and its manufacturing method that can improve the energy density and rate characteristics of the battery even if the amount of active material is increased, as well as an electrode, a battery, a battery module, a battery pack and an electrical device containing the carbon material composite.
[0005] In order to achieve the above-mentioned objectives, the first aspect of the present application provides a carbon material composite, which includes: a carbon material; and magnetic particles distributed on at least a portion of the surface of the carbon material, wherein the carbon material contains nitrogen atoms, and the carbon material is a porous carbon material with an average pore size of 10μm to 80μm, optionally 20μm to 60μm.
[0006] By using the above-mentioned carbon material composite for the electrode membrane, micron-sized through holes of a certain depth can be produced in the membrane, thereby avoiding the occurrence of closed-pore phenomenon caused by too small pore size during the electrode manufacturing process, and can improve the liquid phase mass transfer capacity, which is beneficial to the infiltration and reflux of the electrolyte, accelerates the transmission of ions, reduces liquid phase polarization, increases the depth of electrochemical reaction of the electrode, improves the gram capacity of the active substance, and improves the fast charging performance, thereby improving the energy density and rate performance of the battery; in addition, since the depth of electrochemical reaction of the electrode is increased, the electrode can be formed thicker, and the use of current collectors and diaphragms can be reduced in the same volume of secondary battery casing, so that the cost is greatly reduced.
[0007] In some embodiments, the average particle size of the carbon material is 11 μm to 200 μm, optionally 15 μm to 70 μm. By making the average particle size of the carbon material within the above range, when the carbon material composite is used for a membrane, the energy density and rate performance of the battery can be further improved without affecting the conductive network of the electrode.
[0008] In some embodiments, the magnetic material constituting the magnetic particles is one or more selected from ferroferric oxide, aluminum-nickel-cobalt alloy, iron-chromium-cobalt alloy, and iron-silicon alloy. The average particle size of the magnetic particles is 1nm to 100nm, optionally 1nm to 50nm. By using the above-mentioned magnetic particles with a specific average particle size, when the carbon material composite is used for the diaphragm, a micron-scale through hole of a certain depth can be formed on the diaphragm, which is conducive to the infiltration and reflux of the electrolyte, increases the depth of the electrochemical reaction of the pole piece, and increases the gram capacity of the active substance, thereby further improving the energy density and rate performance of the battery.
[0009] In some embodiments, the mass ratio of the magnetic particles to the carbon material is 2:98 to 5:95. By controlling the mass ratio of the magnetic particles to the carbon material in the carbon material composite within the above range, high energy density and excellent rate performance can be achieved without affecting the performance of the battery.
[0010] In addition, the second aspect of the present application provides a method for manufacturing the carbon material composite according to the first aspect of the present application, which comprises the following steps:
[0011] The step of pickling the carbon source with an acid;
[0012] The step of drying the acid-washed carbon source;
[0013] The step of crushing the dried carbon source to obtain a crushed product;
[0014] A step of carbonizing the pulverized product under an inert gas atmosphere to obtain a carbon material;
[0015] A step of adding magnetic particles and / or a substance capable of becoming magnetic particles to the carbon material and mixing the carbon material thoroughly to obtain a mixture;
[0016] A step of adding the substance that can become magnetic particles or a combination of the magnetic particles and the substance that can become magnetic particles to the carbon material, heating the mixture to make the substance that can become magnetic particles become the magnetic particles and drying the mixture to obtain a carbon material composite; or a step of adding the magnetic particles to the carbon material, drying the mixture to obtain the carbon material composite.
[0017] In some embodiments, the inert gas in the inert gas atmosphere is nitrogen or an inert gas containing nitrogen. By making the inert gas atmosphere of the carbonization process nitrogen or an inert gas containing nitrogen, a porous carbon material containing nitrogen atoms can be obtained.
[0018] In some embodiments, the magnetic material constituting the magnetic particles is selected from one or more of ferroferric oxide, aluminum-nickel-cobalt alloy, iron-chromium-cobalt alloy, and iron-silicon alloy, and the material that can become the magnetic particles is selected from carbonyl iron, orthoferrite, iron-nickel alloy, iron-aluminum alloy, γ-ferric oxide, ferric chloride, cobalt oxide, manganese oxide, BaFe 12 O 19 and one or more of CoMnP.
[0019] In some embodiments, the carbon source is one or more selected from polyurethane and its homologues, polyacrylonitrile and its homologues, carbon nitride, and poly(meth)acrylates. By using the above carbon sources, a porous carbon material containing nitrogen atoms can be obtained.
[0020] In addition, the third aspect of the present application provides a pole piece, which includes a current collector and a membrane arranged on at least one surface of the current collector, and the membrane includes a carbon material composite according to the first aspect of the present application or a carbon material composite produced according to the manufacturing method of the carbon material composite of the second invention of the present application.
[0021] By including the above-mentioned carbon material composite in the diaphragm, through holes of a certain depth are generated in the diaphragm, thereby improving the liquid phase mass transfer capacity, facilitating the infiltration and reflux of the electrolyte, accelerating the transmission of ions, reducing liquid phase polarization, increasing the depth of electrochemical reactions in the electrode, increasing the gram capacity of the active substance, and improving the fast charging performance, thereby improving the energy density and rate performance of the battery; in addition, the use of current collectors and diaphragms can be reduced, thereby greatly reducing costs.
[0022] In some embodiments, the carbon material composite forms through holes on the membrane, and the average depth of the through holes is 20 μm to 200 μm, and optionally 30 μm to 100 μm. By forming through holes of a certain depth on the membrane, the depth of the electrochemical reaction of the pole piece can be increased, the liquid phase mass transfer capacity can be further improved, and the electrolyte infiltration and reflux are more conducive, thereby further improving the energy density and rate performance of the battery.
[0023] In some embodiments, the membrane has an opening rate of 1% to 10%, and optionally 2% to 5%. By making the opening rate of the membrane within the above range, it can be more conducive to the infiltration and reflux of the electrolyte, thereby further improving the energy density and rate performance of the battery.
[0024] In some embodiments, the thickness of the membrane is 200 μm to 1000 μm, and optionally 250 μm to 600 μm. By setting the thickness of the membrane to the above range, the depth of the electrochemical reaction of the electrode can be increased, and the gram capacity of the active material can be increased.
[0025] In some embodiments, the mass percentage of the carbon material composite in the membrane is 0.2% to 10%, optionally 1% to 5%. By including the carbon material composite in the membrane within the above specific range, low cost, high energy density of the battery and excellent rate performance can be achieved without affecting the conductive network of the electrode.
[0026] In some embodiments, the electrode sheet is a positive electrode sheet or a negative electrode sheet, and can be optionally a positive electrode sheet.
[0027] The fourth aspect of the present application provides a battery, comprising: a pole piece according to the third aspect of the present application, or a pole piece having a carbon material composite according to the first aspect of the present application or a carbon material composite made by the manufacturing method of the carbon material composite according to the second aspect of the present application.
[0028] A fifth aspect of the present application provides a battery module, which includes the battery according to the fourth aspect of the present application.
[0029] A sixth aspect of the present application provides a battery pack, which includes a battery module according to the fifth aspect of the present application.
[0030] The seventh aspect of the present application provides a device, which includes at least one of the battery according to the fourth aspect of the present application, the battery module according to the fifth aspect of the present application, or the battery pack according to the sixth aspect of the present application.
[0031] The battery, battery module, battery pack and device of the present application include a pole piece having the carbon material composite provided by the present application, and thus have at least the same advantages as the pole piece. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a structural schematic diagram of an embodiment of the positive electrode plate of the present application.
[0033] Figure 2 is a schematic diagram of a battery according to one embodiment of the present application.
[0034] Figure 3 yes Figure 2 An exploded view of a battery according to one embodiment of the present application is shown.
[0035] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0036] Figure 5 is a schematic diagram of a battery pack according to one embodiment of the present application.
[0037] Figure 6 yes Figure 5 An exploded view of a battery pack according to one embodiment of the present application is shown.
[0038] Figure 7 FIG. 1 is a schematic diagram of a device in which a battery is used as a power source according to an embodiment of the present application.
[0039] Figure 8 is a scanning electron microscope photograph of the carbon material obtained in Preparation Example 1. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the present application clearer, the embodiments of the present application will be described in detail below in conjunction with the accompanying drawings. However, those skilled in the art should understand that these embodiments are only used to illustrate the technical solution of the present application and are not limiting.
[0041] For simplicity, the present application specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0042] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number itself, and "several" in "one or several" means two or more.
[0043] The above-mentioned summary of the invention of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0044] The carbon material composite and its manufacturing method, the electrode sheet, the battery, the battery module, the battery pack and the electric device including the carbon material composite of the present application are described in detail below with reference to the drawings as appropriate.
[0045] Carbon material composites
[0046] The carbon material composite of the present application comprises: a carbon material; and magnetic particles distributed on at least a portion of the surface of the carbon material, wherein the carbon material contains nitrogen atoms, and the carbon material is a porous carbon material with an average pore size of 10 μm to 80 μm, optionally 20 μm to 60 μm.
[0047] It should be noted that the carbon material of the present application is a three-dimensional structure mainly composed of carbon and nitrogen, which may also contain inevitable impurity elements, but is preferably composed only of carbon and nitrogen. In addition, "containing nitrogen atoms in the carbon material" means that nitrogen atoms are bonded as heteroatoms to the ring structure composed of carbon atoms, thereby forming a carbon material with a three-dimensional structure. By constituting the carbon material with carbon and nitrogen, it is beneficial for magnetic particles to be adsorbed on the surface of the carbon material, and a porous material with a specific pore size range can be formed. In addition, the presence of nitrogen in the carbon material can be detected by methods known in the art. For example, infrared spectroscopy can be used to detect whether the carbon material has nitrogen in the form of a carbon-nitrogen bond.
[0048] As the magnetic material constituting the magnetic particles, any material having magnetism may be used, and specifically, alloys of ferromagnetic materials such as nickel (Ni), iron (Fe), and cobalt (Co) (e.g., Co-Fe, Co-Fe-Ni, Ni-Fe, etc.), alloys in which non-magnetic elements (e.g., tantalum, boron, chromium, platinum, silicon, carbon, nitrogen, phosphorus, etc.) are mixed in these alloys (e.g., Co-Fe-B, etc.), oxides containing one or more of Co, Fe, and Ni (e.g., Fe-MnO, etc.), intermetallic compounds known as semi-metallic ferromagnetic materials (Hessler alloys: NiMnSb, Co2MnGe, Co2MnSi, etc.), oxides (e.g., CrO2, Fe3O4, etc.), etc. Among them, from the viewpoint that the magnetic particles can be firmly adsorbed on the surface of the carbon material and micron-level through holes of a certain depth can be formed on the membrane, the magnetic material constituting the magnetic particles is preferably one or more selected from ferromagnetic iron tetroxide, aluminum nickel cobalt alloy, iron chromium cobalt alloy, and iron silicon alloy.
[0049] The carbon material of the present application has micropores with an average pore size of 10μm to 80μm, optionally 20μm to 60μm. By having micropores in the above range in the carbon material, the occurrence of closed-pore phenomenon caused by too small pore size during electrode manufacturing can be avoided, and the liquid phase mass transfer capacity can be improved, which is beneficial to the infiltration and reflux of the electrolyte, accelerates the transmission of ions, and increases the depth of electrochemical reactions in the electrode. In addition, the pore size of the carbon material can be measured by methods known in the art. For example, an electron microscope photograph of the surface of the carbon material is taken using a scanning electron microscope, and the pore sizes of any 30 micropores in the photograph are measured and averaged, which is used as the average pore size of the carbon material.
[0050] By adding a carbon material composite containing magnetic particles in a microporous carbon material with nitrogen atoms to the membrane of the electrode, a micron-sized through hole of a certain depth can be generated in the membrane, thereby avoiding the occurrence of closed-pore phenomenon caused by too small pore size during electrode manufacturing, and improving the liquid phase mass transfer capacity, which is beneficial to the infiltration and reflux of the electrolyte, accelerating the transmission of ions, reducing liquid phase polarization, increasing the depth of the electrochemical reaction of the pole piece, improving the gram capacity of the active material, and improving the fast charging performance, thereby improving the energy density and rate performance of the battery; in addition, due to the increase in the depth of the electrochemical reaction of the pole piece, the pole piece can be formed thicker, and the use of the current collector and the diaphragm can be reduced in the same volume of the secondary battery shell, so that the cost of the battery is greatly reduced. Therefore, according to the carbon material composite of this embodiment, the battery containing it can achieve high energy density and excellent rate performance.
[0051] In the carbon material composite of the present application, the average particle size of the carbon material is 11 μm to 200 μm, and optionally 15 μm to 70 μm. By making the average particle size of the carbon material within the above range, when the carbon material composite is used for the membrane, the energy density and rate performance of the battery can be further improved without affecting the conductive network of the electrode. In addition, the average particle size of the carbon material of the present application can be measured using a laser particle size analyzer.
[0052] In the carbon material composite of the present application, the average particle size of the magnetic particles is 1nm to 100nm, optionally 1nm to 50nm. By using magnetic particles with an average particle size in the above range, when the carbon material composite is used for a diaphragm, micron-sized through holes of a certain depth can be formed on the diaphragm, which is beneficial to the infiltration and reflux of the electrolyte, increases the depth of the electrochemical reaction of the pole piece, and increases the gram capacity of the active substance, thereby further improving the energy density and rate performance of the battery. In addition, the average particle size of the magnetic particles in the carbon material composite of the present application can be measured by methods known in the art. For example, it can be measured by a laser particle size distribution analyzer.
[0053] In the carbon material composite of the present application, the mass ratio of magnetic particles to carbon material is 2:98 to 5:95. By controlling the mass ratio of magnetic particles to carbon material in the carbon material composite within the above range, high energy density and excellent rate performance can be achieved without affecting the performance of the battery. The mass ratio of magnetic particles to carbon material can be controlled by controlling the feed ratio of raw materials in the manufacture of the carbon material composite.
[0054] Method for producing carbon material composite
[0055] The carbon material composite of the present application can be manufactured by a manufacturing method comprising the following steps. Specifically,
[0056] a step of washing the carbon source with an acid (hereinafter, sometimes referred to as “acid washing step”);
[0057] a step of drying the acid-washed carbon source (hereinafter sometimes referred to as a "drying step");
[0058] A step of pulverizing the dried carbon source to obtain a pulverized product (hereinafter, sometimes referred to as a "pulverizing step");
[0059] A step of carbonizing the pulverized product under an inert gas atmosphere to obtain a carbon material (hereinafter, sometimes referred to as a "carbonization step");
[0060] A step of adding magnetic particles and / or a substance capable of becoming magnetic particles to the carbon material and mixing them thoroughly to obtain a mixture (hereinafter, sometimes referred to as a "mixing step");
[0061] A step of adding the substance that can become magnetic particles or a combination of the magnetic particles and the substance that can become magnetic particles to the carbon material, heating the mixture so that the substance that can become magnetic particles becomes the magnetic particles and drying the mixture to obtain a carbon material composite; or a step of adding the magnetic particles to the carbon material, drying the obtained mixture to obtain the carbon material composite (hereinafter sometimes referred to as the "heating and / or drying step").
[0062] Each step is described in detail below.
[0063] [Pickling step]
[0064] The pickling step is a step of pickling the carbon source with an acid. For example, the pickling can be performed by immersing the carbon source in a solution containing an acid for a certain period of time. Impurities such as free radicals in the carbon source can be removed by the pickling step.
[0065] As the carbon source used in the pickling step, substances containing carbon and nitrogen can be listed, specifically, polymers such as polyurethane and its homologues, polyacrylonitrile and its homologues, poly(meth)acrylates, and inorganic substances such as carbon nitride. These can be used alone or in combination of two or more. By using the above-mentioned carbon source, a three-dimensional porous carbon material mainly composed of nitrogen atoms and carbon atoms can be obtained.
[0066] Poly(meth)acrylates refer to polyacrylates and polymethacrylates. Examples of poly(meth)acrylates include poly(meth)alkyl acrylates such as poly(methyl)acrylate and poly(meth)ethyl acrylate; poly(meth)hydroxyalkyl acrylates such as poly(meth)hydroxyethyl acrylate; poly(meth)cycloalkyl acrylates such as poly(meth)cyclohexyl acrylate; and poly(meth)aryl acrylates such as poly(meth)benzyl acrylate.
[0067] As the molecular weight of the carbon source, as long as the number average molecular weight is more than 10000, the upper limit is not particularly limited. In addition, the pore size and particle size of the carbon material finally obtained can be adjusted by adjusting the molecular weight of the carbon source. Specifically, the pore size and particle size of the carbon material can be increased by increasing the molecular weight of the carbon source.
[0068] The acid used in the pickling step is not particularly limited as long as it can remove impurities in the carbon source and does not damage the structure of the carbon source. As such an acid, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, hydrofluoric acid, acetic acid, etc. can be cited. Such an acid can be used alone, or two or more can be used in combination. In addition, as the concentration of the acid, it is not particularly limited as long as it can remove impurities in the carbon source and does not damage the structure of the carbon source.
[0069] [Drying Step]
[0070] The drying step is a step of drying the carbon source after the acid washing step. For example, the carbon source after the acid washing step is dried in an oven at 100 to 120° C., but the present invention is not limited thereto, and any method that can dry the carbon source after the acid washing step without damaging the structure of the carbon source can be used.
[0071] [Crushing Step]
[0072] The pulverizing step is a step of pulverizing the carbon source after the drying step to obtain a pulverized product. In the pulverizing step, the dried carbon source can be pulverized using a pulverizer. Examples of pulverizers include non-media pulverizers such as jet mills; and media pulverizers such as ball mills, bead mills, rod mills, and crushers. The particle size of the pulverized product can be appropriately adjusted according to the particle size of the target carbon material.
[0073] [Carbonization step]
[0074] The carbonization step is a step of heating the pulverized product obtained in the pulverization step in an inert gas atmosphere to carbonize the pulverized product to obtain a carbon material.
[0075] As the inert gas in the inert gas atmosphere, nitrogen or an inert gas containing nitrogen is preferably used. By making the inert gas atmosphere of the carbonization process nitrogen or an inert gas containing nitrogen, a porous carbon material mainly composed of nitrogen atoms and carbon atoms can be obtained. In addition, as a source of nitrogen atoms, in addition to nitrogen, a nitrogen-containing compound such as carbazole can be further added to form a porous material composed of nitrogen atoms and carbon atoms.
[0076] The carbonization temperature is not particularly limited as long as it is a temperature at which the carbon source can be carbonized, and for example, 500 to 1000° C. can be cited, preferably 600 to 900° C. If the temperature is too low, there is a problem of too long carbonization time and insufficient carbonization. If the temperature is too high, the equipment load becomes high and the economic benefit is reduced. As the carbonization time, for example, 6 to 12 hours can be cited, preferably 7 to 10 hours, and more preferably 8 to 10 hours.
[0077] In addition, the pore size of the obtained carbon material can be adjusted by using an alkali such as potassium hydroxide or sodium hydroxide during the carbonization process.
[0078] [Mixing Step]
[0079] The mixing step is a step of adding magnetic particles and / or a substance that can become magnetic particles to the carbon material obtained in the carbonization step and mixing them thoroughly to obtain a mixture.
[0080] As the magnetic material constituting the magnetic particles, the magnetic materials listed in the carbon material composite can be cited, and the preferred magnetic materials are the same as the preferred cases listed above. The average particle size of the added magnetic particles is 1 to 100 nm, and optionally 1 to 50 nm.
[0081] As the substance that can be used as the magnetic particle, there are listed substances that can be used as the above-mentioned magnetic material, among which carbonyl iron, ferrite, iron-nickel alloy, iron-aluminum alloy, γ-iron trioxide, iron trichloride, cobalt oxide, manganese trioxide, BaFe 12 O 19 and one or more of CoMnP.
[0082] Examples of the mixing method used in the mixing step include mixing using ultrasound and mixing using a homogenizer, but the method is not particularly limited.
[0083] [Heating and / or drying step]
[0084] In the case where a substance that can become magnetic particles or a combination of magnetic particles and substances that can become magnetic particles is added to the carbon material, the heating and / or drying step is a step of heating the mixture obtained in the mixing step to make the substance that can become magnetic particles become magnetic particles and drying it to obtain a carbon material composite; or in the case where magnetic particles are added to the carbon material, the heating and / or drying step is a step of drying the mixture obtained in the mixing step to obtain a carbon material composite.
[0085] When a substance that can become magnetic particles or a combination of magnetic particles and a substance that can become magnetic particles is added to a carbon material, the temperature to which the mixture obtained in the mixing step is heated can be any temperature that can turn the substance that can become magnetic particles into magnetic particles. There is no particular limitation on the temperature, and examples thereof include 150 to 300°C, preferably 160 to 280°C, more preferably 160 to 260°C, and further preferably 160 to 240°C.
[0086] In the heating and / or drying step, the mixture of the magnetic particles and the carbon material may be dried by placing it in an oven, but the present invention is not limited thereto, and any method may be used as long as the mixture can be dried without destroying the structure of the carbon material.
[0087] The final carbon material composite mainly contains carbon material and magnetic particles. Since the particle size of the magnetic particles is nanometer-scale, the pore size of the carbon material composite is basically equal to the pore size of the carbon material, and the particle size of the carbon material composite is basically equal to the particle size of the carbon material.
[0088] Battery
[0089] The battery in this application refers to a battery that can be used continuously by activating the active material by charging after the battery is discharged. Generally, the battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, the active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which can insulate the electrons and prevent internal short circuits. At the same time, it allows the active ions to pass through and move between the positive and negative electrodes, playing an isolation role. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0090] The carbon material composite of the present application can be used in the membrane of the positive electrode sheet and / or the negative electrode sheet, preferably in the membrane of the positive electrode sheet. By including the above-mentioned carbon material composite in the membrane of the positive electrode sheet and / or the negative electrode sheet, a certain depth of micron-level through holes can be generated in the membrane, thereby avoiding the occurrence of closed-pore phenomenon in the electrode manufacturing process, and improving the liquid phase mass transfer capacity, which is conducive to the infiltration and reflux of the electrolyte, speeding up the transmission of ions, reducing liquid phase polarization, increasing the depth of the electrochemical reaction of the electrode sheet, improving the gram capacity of the active substance, and improving the fast charging performance, thereby improving the energy density and rate performance of the battery; in addition, the use of the current collector and the diaphragm can be reduced, so that the cost of the battery is greatly reduced.
[0091] In addition, the battery of the present application may be any one of a lithium ion battery, a metal lithium battery, and the like.
[0092] [Positive electrode]
[0093] Figure 1 Schematic diagram of the structure of an embodiment of the positive electrode sheet of the present application. Figure 1 As shown, the positive electrode sheet 100 of the present application includes a positive electrode current collector 20 and a positive electrode film 10 arranged on one surface of the positive electrode current collector in the thickness direction. In addition, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode film can also be arranged on two opposite surfaces of the positive electrode current collector.
[0094] The positive electrode diaphragm 10 includes micrometer-sized through holes 11 formed by the carbon material composite of the present application. By including the above-mentioned carbon material composite in the diaphragm, an external magnetic field is applied during the manufacturing process of the positive electrode diaphragm to orient part of the carbon material composite in the depth direction of the diaphragm, thereby generating through holes of a certain depth in the diaphragm, improving the liquid phase mass transfer capacity, facilitating the infiltration and reflux of the electrolyte, accelerating the transmission of ions, reducing liquid phase polarization, increasing the depth of the electrochemical reaction of the electrode, increasing the gram capacity of the positive electrode active material, and improving the fast charging performance, thereby improving the energy density and rate performance of the battery.
[0095] Through holes are formed on the diaphragm by a carbon material composite, and the average depth of the through holes is 20μm to 200μm, and optionally 30μm to 100μm. By forming through holes of a certain depth on the diaphragm, the depth of the electrochemical reaction of the pole piece can be increased, the liquid phase mass transfer capacity can be further improved, and it is more conducive to the infiltration and reflux of the electrolyte, thereby further improving the energy density and rate performance of the battery. In the present application, the average depth of the through hole can be adjusted by adjusting the size of the external magnetic field, the particle size of the carbon material, etc. In addition, the average depth of the through hole can be measured by using ion polishing and scanning electron microscopy.
[0096] In some embodiments, the thickness of the membrane is 200 μm to 1000 μm, and optionally 250 μm to 600 μm. By setting the thickness of the membrane to the above range, the depth of the electrochemical reaction of the electrode can be increased, and the gram capacity of the active material can be increased.
[0097] In some embodiments, the opening rate of the through holes formed by the carbon material composite on the membrane is 1% to 10%, and optionally 2% to 5%. By making the opening rate within the above range, it can be more conducive to the infiltration and reflux of the electrolyte, thereby further improving the energy density and rate performance of the battery.
[0098] In some embodiments, the mass percentage of the carbon material composite in the membrane is 0.2% to 10%, and optionally 1% to 5%. By including the carbon material composite in the membrane within the above specific range, low cost, high energy density of the battery and excellent rate performance can be taken into account without affecting the conductive network of the electrode, and the amount of current collector and separator used can be reduced, so that the cost of the battery is greatly reduced.
[0099] The positive electrode film of the present application also includes a positive electrode active material. The positive electrode active material may include, but is not limited to, lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide, lithium titanate, etc. The positive electrode active material may use one or more of these.
[0100] The positive electrode membrane of the present application also includes an optional binder and a conductive agent. The present invention does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0101] As an example, the binder may include one or more selected from styrene-butadiene rubber (SBR), water based acrylic resin, carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), ethylene-vinyl acetate copolymer (EVA) and polyvinyl alcohol (PVA). The conductive agent may include one or more selected from graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0102] In the battery of the present application, the positive electrode current collector may be a metal foil, a porous metal plate or a composite current collector. As metal foil and porous metal plate, for example, foil or porous plate of metals such as aluminum, copper, nickel, titanium or silver or their alloys can be used, preferably aluminum foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.). The thickness of the positive electrode current collector is 5μm to 20μm, preferably 6μm to 18μm, and more preferably 8μm to 16μm.
[0103] The positive electrode sheet of the present application can be prepared according to the common methods in the art. For example, the carbon material composite, the positive electrode active material, the optional conductive agent, the optional binder and any other components can be dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; under the condition of applying an external magnetic field, the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0104] [Negative electrode]
[0105] In the battery of the present application, the negative electrode sheet generally includes a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode film sheet is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0106] Similar to the above-mentioned positive electrode sheet, the negative electrode membrane may also contain the carbon material composite of the present application. Thus, a micron-sized through hole formed by the carbon material composite of the present application with a certain depth is generated in the negative electrode membrane. Thus, the liquid phase mass transfer capacity is improved, which is conducive to the infiltration and reflux of the electrolyte and increases the depth of the electrochemical reaction of the electrode sheet.
[0107] In the negative electrode sheet, the average depth of the through holes, the porosity, the thickness of the membrane, and the content of the carbon material composite are the same as those in the positive electrode sheet, and the preferred conditions are also the same.
[0108] In the battery of the present application, the negative electrode current collector can be made of materials such as metal foil, porous metal plate or composite current collector. For example, as metal foil or porous metal plate, foil or porous plate of metals such as copper, nickel, titanium or iron or their alloys can be used, preferably copper foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0109] In the battery of the present application, the negative electrode membrane generally further includes a negative electrode active material and optional conductive agent, binder and thickener.
[0110] The negative electrode active material can use the negative electrode active material commonly used in the art for preparing the negative electrode of the battery, for example, it can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy and one or more of metallic lithium.
[0111] As an example, the conductive agent may include one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0112] As an example, the binder may include one or more of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin, and carboxymethyl cellulose (CMC).
[0113] As an example, the thickener may be carboxymethyl cellulose (CMC) or the like.
[0114] The present application is not limited to these materials, and other materials that can be used as batteries in addition to negative electrode active materials, conductive agents, binders and thickeners can also be used in the present application.
[0115] The negative electrode sheet of the present application can be prepared according to the common methods in the art. Specifically, the carbon material composite, the negative electrode active material and the optional conductive agent, binder and thickener are dispersed in a solvent to form a uniform negative electrode slurry, and then, the negative electrode slurry is coated on the negative electrode current collector under the condition of applying an external magnetic field, and the negative electrode is obtained through drying, cold pressing and other processes. The solvent can be N-methylpyrrolidone (NMP) or deionized water.
[0116] [Electrolyte]
[0117] The electrolyte of the present application includes an organic solvent, an electrolyte lithium salt and an additive. The present application does not specifically limit the types of the organic solvent and the electrolyte lithium salt, and they can be selected according to actual needs.
[0118] As an example, the solvent can be one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE), and it is preferred to use two or more.
[0119] As an example, the electrolyte lithium salt can be one or more selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0120] The electrolyte may also optionally include an additive. The additive may be any additive that can be used in a battery, and is not specifically limited thereto, and may be selected according to actual needs. As an example, the additive may include one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), succinonitrile (SN), adiponitrile (AND), 1,3-propylene sultone (PST), sulfonate cyclic quaternary ammonium salt, tris(trimethylsilyl) phosphate (TMSP) and tris(trimethylsilyl) borate (TMSB).
[0121] The electrolyte can be prepared according to a common method in the art. Specifically, an organic solvent, an electrolyte lithium salt and an optional additive can be mixed uniformly to obtain an electrolyte. There is no particular restriction on the order of adding the substances. For example, an electrolyte lithium salt and an optional additive can be added to an organic solvent and mixed uniformly to obtain an electrolyte.
[0122] In addition, as the electrolyte of the present application, in addition to the electrolyte prepared by the above method, a commercially available product may be used, for example, 8950FB manufactured by Guotai Huarong Chemical New Materials Co., Ltd.
[0123] [Isolation film]
[0124] The present application has no particular restrictions on the type of separator, and any known porous separator with electrochemical stability and chemical stability for lithium ion batteries or lithium metal batteries can be selected. For example, the separator can be one or more selected from glass fiber film, non-woven film, polyethylene film, polypropylene film, polyvinylidene fluoride film, and multilayer composite films containing one or more of them.
[0125] In some embodiments, the positive electrode sheet, the separator and the negative electrode sheet are stacked in order, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, to obtain an electrode assembly, and the electrode assembly is placed in an outer package, and the electrolyte is injected and sealed to obtain a lithium-ion battery or a metal lithium battery. In addition to the above-mentioned stacking process, the positive electrode sheet, the separator and the negative electrode sheet can also be obtained by a winding process to obtain an electrode assembly.
[0126] In some embodiments, the outer packaging of a battery such as a lithium-ion battery or a metal lithium battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0127] The present application has no particular limitation on the shape of the battery, which may be cylindrical, square or any other shape. Figure 2 A lithium-ion battery 5 having a square structure is used as an example.
[0128] In some embodiments, reference Figure 3The outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the lithium-ion battery 5 can be one or more, which can be adjusted according to demand.
[0129] In some embodiments, lithium-ion secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0130] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of lithium-ion batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of batteries 5 may be fixed by fasteners.
[0131] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of batteries 5 are received in the receiving space.
[0132] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0133] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0134] Device
[0135] Another aspect of the present application provides a device, the device comprising at least one of the battery, battery module, or battery pack provided in the present application. The battery can be used as a power source for the device, and can also be used as an energy storage unit for the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0136] The device can select batteries, battery modules or battery packs according to its usage requirements.
[0137] Figure 7 The device is used as an example. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0138] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion secondary battery may be used as a power source.
[0139] Example
[0140] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are conventional products that can be obtained commercially without specifying the manufacturer. The content of each component in the embodiments of the present application, if not otherwise specified, is by mass.
[0141] Preparation Example 1
[0142] 10g of polyurethane (manufactured by Aladdin, molecular weight 50000) was soaked in a 1mol / L mixed acid solution of phosphoric acid and hydrochloric acid for 10 hours. The soaked material was placed in an oven at 100°C and dried for 4 hours. The dried material was put into a ball mill together with ZnO, metal Mg and potassium acetate, and crushed at 500r / min for 4 hours. The crushed material was placed in a tubular furnace, and carbonized at 500°C for 12 hours under a nitrogen atmosphere while passing carbon dioxide. Iron oxide powder (particle size: 50nm) was added to the carbonized carbon material and ultrasonically mixed for 4 hours to obtain a mixture. The obtained mixture was placed in a vacuum oven and dried at 160°C for 4 hours to obtain a carbon material composite 1.
[0143] Preparation Examples 2 to 11
[0144] Carbon material composites 6, 7, 9 to 16 were manufactured in the same manner as in Preparation Example 1, except that the type of carbon source used, the type of acid in the pickling step, the type of nitrogen source, the carbonization temperature, the carbonization time, the type of magnetic particles or substances that can become magnetic particles, and the temperature and time of the heating and drying steps were changed as shown in Table 1.
[0145] In addition, carbon material composites 2 to 5 and 8 were produced in the same manner as in Preparation Example 1 except that production conditions such as the carbonization temperature and the carbonization time were changed.
[0146]
[0147] The carbon material obtained after the carbonization step in Preparation Example 1 was photographed using a scanning electron microscope. The obtained photograph (magnification: 1000 times) is shown in Figure 8 In. According to Figure 8 It can be seen that through the carbonization step, a carbon material with micron-sized pores can be obtained.
[0148] Furthermore, for each carbon material composite obtained above, the average pore diameter, average particle diameter, and average particle diameter of the carbon material can be measured by the following method. In addition, the presence of carbon element in the carbon material composite was detected by the following method, and the obtained results are shown in the following Table 2.
[0149] 1. Determination of average pore size of carbon materials
[0150] Each carbon material composite obtained was photographed at a magnification of 1000 times using a scanning electron microscope (SEM), and the pore sizes of any 30 micropores in the obtained photographs were measured and averaged to obtain the average pore size of the carbon material composite. Since the particle size of the magnetic particles is nanometer-level, the pore size of the carbon material composite is substantially equal to the pore size of the carbon material, and thus the average pore size of the carbon material composite is taken as the average pore size of the carbon material.
[0151] 2. Determination of average particle size of carbon materials
[0152] For each obtained carbon material composite, the average particle size D50 of the carbon material composite was measured using a laser particle size analyzer (model: Malvern Master Size 3000) with reference to the standard GB / T 19077.1-2016. Since the particle size of the magnetic particles is nanometer-scale, the average particle size of the carbon material composite is substantially equal to the average particle size of the carbon material, and thus, the average particle size D50 of the carbon material composite is taken as the average particle size of the carbon material.
[0153] 3. Determination of the average particle size of magnetic particles
[0154] When magnetic particles were added, the average particle size D50 of the raw material magnetic particles was measured using a laser particle size analyzer (model: Malvern Master Size 3000) in accordance with standard GB / T 19077.1-2016, and this was taken as the average particle size of the magnetic particles in the carbon material composite.
[0155] When a substance capable of becoming magnetic particles was added, the average particle size D50 of the magnetic particles in each obtained carbon material composite was measured using a laser particle size analyzer (model: Malvern Master Size 3000) with reference to the standard GB / T 19077.1-2016.
[0156] 4. Detection of nitrogen
[0157] For the carbon material obtained after the carbonization step, an infrared spectrometer is used to obtain an infrared spectrum. For the obtained spectrum, if there is a displacement of the carbon-nitrogen bond, it is determined that there is nitrogen in the carbon material; if there is no displacement of the carbon-nitrogen bond, it is determined that there is no nitrogen in the carbon material.
[0158] Example 1
[0159] Preparation of positive electrode
[0160] The positive electrode active material LiNi 0.96 Co 0.02 Mn 0.02 O2 (NCM96), the carbon material composite 1 prepared above, conductive carbon black (Super-P) and carbon nanotubes as a conductive agent, and polyvinylidene fluoride as a binder are added to N-methylpyrrolidone in a mass ratio of 93:5:0.6:0.2:1.2, and stirred thoroughly to prepare a slurry with a solid content of 68%. The obtained slurry is applied to the surface of both sides of a 10μm aluminum foil as a current collector under the condition of applying an external magnetic field by a magnet, and after drying and cold pressing, a positive electrode sheet is obtained.
[0161] Preparation of negative electrode
[0162] The negative electrode active material SiO, the conductive agent conductive carbon black (Super-P) and the carbon nanotubes, and the sodium carboxymethyl cellulose were mixed in a mass ratio of 96.8:1.04:0.06:2.1, added into deionized water, and fully stirred to form a uniform negative electrode slurry. The obtained negative electrode slurry was coated on the surface of the negative electrode current collector 4.5 μm copper foil, and dried, cold pressed, slit, and cut to obtain a negative electrode sheet.
[0163] Isolation film
[0164] A polyethylene film was used as a separator.
[0165] Preparation of electrolyte
[0166] Trade name 8950FB manufactured by Guotai Huarong Chemical New Materials Co., Ltd. was used as an electrolyte.
[0167] Preparation of batteries
[0168] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, the separator is placed between the positive and negative electrodes to play a role of isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an outer package, the prepared electrolyte is injected and packaged to obtain a battery.
[0169] (Examples 2 to 19 and Comparative Examples 1 to 5)
[0170] The preparation method is similar to that of Example 1, except that different carbon material composites or different contents of the carbon material composites are used in the membrane, as shown in Table 2 below.
[0171] The following parameter measurements were performed on the membranes of Examples 1 to 19 and Comparative Examples 1 to 5, and the obtained results are shown in Table 3 below.
[0172] 1. Determination of the average depth of through holes
[0173] The obtained carbon material composite was cut, and the cross section was ion polished. The depths of the through holes at 10 locations were measured using a scanning electron microscope, and the averaged values were taken as the average depth of the through holes.
[0174] 2. Determination of open porosity
[0175] The porosity of the membrane was calculated using the following formula.
[0176] Opening ratio = N × π (R / 2) 2 / S
[0177] Wherein, N is the number of through holes on the membrane, R is the average pore size of the carbon material composite in the membrane, and S is the area of the membrane.
[0178] In addition, the following performance tests were conducted on the batteries obtained in Examples 1 to 19 and Comparative Examples 1 to 5, and the obtained results are shown in Table 3 below.
[0179] 1. Determination of energy density
[0180] The obtained battery was left to stand at a high temperature of 45°C for 24 hours. The battery after high temperature standing was left to stand for 12 hours, then charged to 3.5V at a constant current of 0.02C, then discharged to 4.6V at a constant current of 0.1C, and then charged to a current of 0.02C at a constant voltage of 4.6V, and left to stand for 3 minutes, and then discharged to 2.5V at a constant current of 0.1C again, and sealed by decompression, thereby performing the battery capacity division. The battery after capacity division was left to stand for 5 minutes, and charged to 4.25V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage, and after standing for 5 minutes, discharged to 2.5V at a constant current of 0.5C, and the actual capacity at this time was recorded, and the obtained value was divided by the mass of the battery to obtain the energy density (unit: W·h / kg).
[0181] 2. Determination of rate performance
[0182] At 25°C, after the battery has been fully charged, let it stand for 30 minutes, then discharge it to 2.0V at a constant current of 0.1C. After standing for 1 hour, charge it to 4.25V at a constant current of 0.1C. Then, let it stand for 30 minutes, discharge it to 2.0V at a constant current of 0.1C. Let it stand for 1 hour, charge it to 4.25V at a constant current of 0.1C, charge it to 0.02C at a constant voltage, and record its actual capacity as C0. Next, discharge it to 2.0V at a constant current of 0.2C, let it stand for 1 hour, charge it to 4.25V at a constant current of 0.1C, charge it to 0.02C at a constant voltage, let it stand for 30 minutes, discharge it to 2.0V at a constant current of 0.33C, and record its actual capacity as C1. C1 / C0 is used as the rate characteristic at 0.33C. Next, let it stand for 1 hour, charge to 4.25V at 0.1C constant current, charge to 0.02C at constant voltage, let it stand for 30 minutes, discharge to 2.0V at 0.5C constant current, and let it stand for 1 hour. Then, charge to 4.25V at 0.1C constant current, charge to 0.02C at constant voltage, let it stand for 30 minutes, discharge to 2.0V at 1C constant current, let it stand for 1 hour, charge to 4.25V at 0.1C constant current, charge to 0.02C at constant voltage, let it stand for 30 minutes, discharge to 2.0V at 2C constant current, let it stand for 1 hour, record the actual capacity C2 at this time, and use C2 / C0 as the rate characteristic at 2C.
[0183]
[0184]
[0185] According to the results in Table 3, in the case of not having the carbon material composite of the present application, although there is no loss of active material and the energy density is high, the rate characteristics at 0.33C and the rate characteristics at 2C are both poor. In addition, in the case where the carbon material in the carbon material composite does not contain nitrogen atoms, although the rate characteristics at 0.33C are improved, the rate characteristics at 2C are still poor. In addition, in the case where the carbon material composite does not contain magnetic particles, the rate characteristics at 2C are also poor. Further, in the case where the average pore size of the carbon material composite is not within the scope of the present application, the rate characteristics at 0.33C and the rate characteristics at 2C are both poor. On the other hand, in the case of having the carbon material composite of the present application, both high energy density and excellent rate characteristics can be taken into account.
[0186] Embodiment 20
[0187] A battery was manufactured in the same manner as in Example 1, except that no carbon material composite was added to the positive electrode membrane and 3% of carbon material composite 1 was added to the negative electrode membrane. The parameters of the membrane and the performance of the battery were evaluated in the same manner as in Example 1. The results are shown in Table 4 below.
[0188] [Table 4]
[0189]
[0190] According to the results in Table 4, when the negative electrode membrane contains the carbon material composite of the present application, both high energy density and excellent rate characteristics can be achieved compared to the case where the negative electrode membrane does not contain the carbon material composite.
[0191] Those skilled in the art should understand that the above-mentioned embodiments are only some specific embodiments for implementing the present application, and in actual applications, various changes and modifications may be made thereto in form and details, all of which fall within the scope of protection of the present application.
Claims
1. A carbon material composite, in, include: Carbon materials; and magnetic particles distributed on at least a portion of the surface of the carbon material, wherein the carbon material contains nitrogen atoms, The carbon material is a porous carbon material with an average pore diameter of 10 μm to 80 μm.
2. The carbon material composite according to claim 1, wherein The carbon material is a porous carbon material with an average pore diameter of 20 μm to 60 μm.
3. The carbon material composite according to claim 1, wherein The average particle size of the carbon material is 11 μm to 200 μm.
4. The carbon material composite according to any one of claims 1 to 3, wherein The average particle size of the carbon material is 15 μm to 70 μm.
5. The carbon material composite according to any one of claims 1 to 3, wherein The magnetic material constituting the magnetic particles is at least one selected from the group consisting of ferroferric oxide, aluminum-nickel-cobalt alloy, iron-chromium-cobalt alloy, and iron-silicon alloy.
6. The carbon material composite according to any one of claims 1 to 3, wherein The average particle size of the magnetic particles is 1 nm to 100 nm.
7. The carbon material composite according to any one of claims 1 to 3, wherein The average particle size of the magnetic particles is 1 nm to 50 nm.
8. The carbon material composite according to any one of claims 1 to 3, wherein The mass ratio of the magnetic particles to the carbon material is 2:98 to 5:
95.
9. A method for producing a carbon material composite according to any one of claims 1 to 8, wherein: The following steps are included: The step of pickling the carbon source with an acid; The step of drying the acid-washed carbon source; The step of crushing the dried carbon source to obtain a crushed product; A step of carbonizing the pulverized product under an inert gas atmosphere to obtain a carbon material; A step of adding magnetic particles and / or a substance capable of becoming magnetic particles to the carbon material and mixing the carbon material thoroughly to obtain a mixture; A step of adding the substance that can become magnetic particles or a combination of the magnetic particles and the substance that can become magnetic particles to the carbon material, heating the mixture to make the substance that can become magnetic particles become the magnetic particles and drying the mixture to obtain a carbon material composite; or a step of adding the magnetic particles to the carbon material, drying the mixture to obtain the carbon material composite.
10. The method for producing a carbon material composite according to claim 9, wherein: The inert gas in the inert gas atmosphere is nitrogen or an inert gas containing nitrogen.
11. The method for producing a carbon material composite according to claim 9 or 10, wherein: The magnetic material constituting the magnetic particles is one or more selected from ferroferric oxide, aluminum-nickel-cobalt alloy, iron-chromium-cobalt alloy, and iron-silicon alloy; The material that can be used as magnetic particles is selected from carbonyl iron, ferrite, iron-nickel alloy, iron-aluminum alloy, γ-iron trioxide, iron trichloride, cobalt oxide, manganese trioxide, BaFe 12 O 19 and one or more of CoMnP.
12. The method for producing a carbon material composite according to claim 9 or 10, wherein: The carbon source is one or more selected from polyurethane and its homologues, polyacrylonitrile and its homologues, carbon nitride, and poly(meth)acrylates.
13. A pole piece, wherein: include: a current collector and a membrane disposed on at least one surface of the current collector, The membrane comprises the carbon material composite according to any one of claims 1 to 8 or the carbon material composite produced by the method for producing the carbon material composite according to any one of claims 9 to 12.
14. The pole piece according to claim 13, wherein: Through holes are formed on the membrane by the carbon material composite, and the average depth of the through holes is 20 μm to 200 μm.
15. The pole piece according to claim 13, wherein: Through holes are formed on the membrane by the carbon material composite, and the average depth of the through holes is 30 μm to 100 μm.
16. The pole piece according to any one of claims 13 to 15, wherein: The opening rate of the membrane is 1% to 10%.
17. The pole piece according to any one of claims 13 to 15, wherein: The opening rate of the membrane is 2% to 5%.
18. The pole piece according to any one of claims 13 to 15, wherein: The thickness of the membrane is 200 μm to 1000 μm.
19. The pole piece according to any one of claims 13 to 15, wherein: The thickness of the membrane is 250 μm to 600 μm.
20. The pole piece according to any one of claims 13 to 15, wherein: The mass percentage of the carbon material composite in the membrane is 0.2% to 10%.
21. The pole piece according to any one of claims 13 to 15, wherein: The mass percentage of the carbon material composite in the membrane is 1% to 5%.
22. The pole piece according to any one of claims 13 to 15, wherein: The pole piece is a positive pole piece or a negative pole piece.
23. The pole piece according to any one of claims 13 to 15, wherein: The pole piece is a positive pole piece.
24. A battery comprising: a pole piece according to any one of claims 13 to 23, or a pole piece having the carbon material composite according to any one of claims 1 to 8 or a carbon material composite produced by the method for producing the carbon material composite according to any one of claims 9 to 12.
25. A battery module comprising the battery according to claim 24.
26. A battery pack comprising the battery module according to claim 25.
27. An electrical device comprising at least one of the battery according to claim 24, the battery module according to claim 25, or the battery pack according to claim 26.
Citation Information
Patent Citations
Fe3O4 / C composite material, its preparation method and its application in lithium ion battery
CN103825019A
Three-dimensional structured micropore material and preparation method therefor
CN107369521A